Atrazine degradation patterns: the role of straw cover and herbicide application history - Leal,Daniela Piaz Barbosa (2019)
ABSTRACT: In Brazil, atrazine (ATZ) is widely applied to maize (Zea mays L.) fields for weed control. The presence of ATZ and its metabolites in soil and water matrices has become a matter of some concern for governmental authorities as well as for society at large. This study evaluated the patterns of ATZ degradation (mineralization, extractable and non-extractable ATZ residues, and metabolite formation) in a Brazilian Typic Paleudult. Soil samples from a cultivated area under a no-tillage system with a history of ATZ application were incubated with 14C-ATZ in both the presence and absence of straw cover on the soil surface, and the evolved 14CO2 was determined by liquid scintillation. Samples from an area with native vegetation, adjacent to the cultivated area, were also incubated as a control. A higher mineralization of ATZ was observed in the cultivated soil (> 85 %) in comparison with the native soil (10 %) after 85 days of incubation. In addition to the higher mineralization and hydroxyatrazine (HA) formation, a rapid decrease in the water-extractable residues was observed in the cultivated soil. When the cultivated soil was covered with straw, mineralization was reduced by up to 30 % although a small amount of remobilization to the soil occurred within the 85 days. Straw cover hindered the degradation of ATZ in cultivated soils; whereas an accelerated biodegradation was due to repeated applications of ATZ, which may have selected microbiota more skilled at biodegrading the herbicide.